Blood Pressure Assessment in Adults in Clinical Practice and Clinic-Based Research: JACC Scientific Expert Panel - Muntner, Paul (J Am Coll Cardiol, 2019)
The accurate measurement of blood pressure (BP) is essential for the diagnosis and management of hypertension. Restricted use of mercury devices, increased use of oscillometric devices, discrepancies between clinic and out-of-clinic BP, and concerns about measurement error with manual BP measurement techniques have resulted in uncertainty for clinicians and researchers. The National Heart, Lung, and Blood Institute of the US National Institutes of Health convened a Working Group of clinicians and researchers in October 2017 to review data on BP assessment among adults in clinical practice and clinic-based research. In this report, we review the topics discussed during a two-day meeting including the current state of knowledge on BP assessment in clinical practice and clinic-based research, knowledge gaps pertaining to current BP assessment methods, research and clinical needs to improve BP assessment, and the strengths and limitations of using BP obtained in clinical practice for research and quality improvement activities.